RADON CHANGES ALONG MAIN FAULTS IN THE BROADER AIGION REGION, NW PELOPONNESE - Katsanou, K.; Stratikopoulos, K.; Zagana, E.; Lambrakis, N. (Bulletin of the Geological Society of Greece, 2010)
In the present study the relationship between Rn and hydrochemical parameters in groundwater samples with the intense tectonics that prevail in the broader region of Aigion were investigated. Radon concentrations were measured in water samples collected from the unconfined aquifer, hosted in Plio-Pleistocene deposits, along the major faults of the research area. The spatial distribution of radon concentrations revealed the existence of three distinct zones along Aigion, Pyrgaki and Helike faults, respectively. The first two zones are characterized by high radon concentrations, whereas the third by low radon concentrations. It is also shown that 222Rn and CO2 concentrations display similar spatial distribution suggesting a common origin for these two gases, with CO2 being the major carrier gas for radon in deep fluids. The deformation and fragmentation of rocks along the fault zones enables the circulation of those fluids resulting in elevated radon concentrations in groundwater. However, other factors, such as the mineralogical composition of the sediments along the fault planes may restrict this process. The distribution of radon along the fault zones suggests that radon measurements can be used as a tool for the detailed mapping of active faults and if combined with seismic data even as a tool for study earthquake prediction.